Acute limb ischemia in patient with COVID-19 infection - Putra, Agus Dody Pranata Suadi; Riani, Ni Wayan Anantika; Wiradana, A. A. Gde Agung Anom Arie (International Journal of Advances in Medicine, 2023)
The severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease 2019 caused a worldwide pandemic and became a massive problem in our healthcare system. This infection has broad clinical presentation from asymptomatic to severe symptoms, and unfortunately death. Hypercoagulability associated with this infection can cause a significant morbidity, that increased risk of microthrombosis, vascular hyperpermeability, disseminated intravascular coagulation, and multiorgan failure. Acute limb ischemia (ALI) is the one of coronavirus disease 2019 associated coagulopathy that threaten the limb viability in a very short interval. We report a case of a 98-year-old woman with coronavirus disease 2019 infection, then suddenly has ALI in the right foot.